(untitled) (Delta Medical College Journal, 2015)
Background: Estimation of intercanthal width and biocular breadth from digital photography is important in the evaluation of several systemic syndromes, craniofacial abnormalities and in surgical treatments of post-traumatic telecanthus. Dysmorphologists employ canthal measurements in evaluating the degree of hypertelorism. So intercanthal width and biocular breadth values are very important for clinicians, ophthalmologists, plastic and reconstructive surgeons. The reliability of estimation of intercanthal width from biocular breadth by using multiplication factor is high. Objective: To make an attempt to determine the multiplication factor for estimation of intercanthal width. Materials and method: This is a cross sectional study conducted in the Anatomy department of Sir Salimullah Medical College, Dhaka, Bangladesh from January 2010 to June 2011. One hundred Bangladeshi 25 to 45 years old women were selected purposively for the study. Results: The mean±SD intercanthal width was 3.456±0.3585 cm. Multiplication factor for measuring intercanthal width from biocular breadth (9.348±0.7174 cm) was 0.369±0.0232 cm. The mean±SD of estimated intercanthal width was 3.449±0.2647 cm. No significant difference was found between the measured and estimated intercanthal width. Conclusion: Multiplication factor can be used to determine intercanthal width in Bangladeshi women though agreement test would have been done to generalize the finding. Delta Med Col J. Jul 2015; 3(2): 78-82